2017
DOI: 10.1071/an17349
|View full text |Cite
|
Sign up to set email alerts
|

Recent findings regarding calcium and phytase in poultry nutrition

Abstract: Calcium (Ca) is an essential element for poultry and even a mild deficiency can lead to significant welfare and performance issues. As a result, it is often fed at levels in excess of requirement, partly as an insurance policy and, to some degree, because of its relatively low cost compared with other feed ingredients. However, when diets meet but do not exceed the phosphorus (P) requirements of the bird, a marginal Ca excess can interfere with P digestibility. This problem is exacerbated when phytases are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The higher degradation in the challenged birds might have been necessitated by either the lower pH recorded in the ileum at d 29 or lower feed (phytate) intake at d 28 as reported ( Zanu et al, 2020a ). The lower the pH, the less negatively charged IP6 becomes, and its ability to chelate positively charged ions is reduced ( Bedford and Rousseau, 2017 ). This suggests that at a higher ileal pH as detected in the unchallenged birds in this study, potential chelators might have been precipitated by phytate and decreased hydrolysis by phytase.…”
Section: Discussionmentioning
confidence: 99%
“…The higher degradation in the challenged birds might have been necessitated by either the lower pH recorded in the ileum at d 29 or lower feed (phytate) intake at d 28 as reported ( Zanu et al, 2020a ). The lower the pH, the less negatively charged IP6 becomes, and its ability to chelate positively charged ions is reduced ( Bedford and Rousseau, 2017 ). This suggests that at a higher ileal pH as detected in the unchallenged birds in this study, potential chelators might have been precipitated by phytate and decreased hydrolysis by phytase.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study corroborate with many reports that even in diets supplemented with phytase, the incremental concentration of Ca increases residual concentration not only of IP6 but also IP5, IP4, and IP3 as well ( Zeller et al., 2015 ; Li et al., 2016 ; Beeson et al., 2017 ). Bedford and Rousseau (2017) had argued that a severely imbalanced diet (in the case of this work, a wide Ca:P) might compromise the response of high dietary phytase because such imbalances inhibit the conversion of IP6 to the lower esters. The results therefore suggest that to dephosphorylate IP6 ultimately to inositol, high levels of phytase with a low dietary Ca level (or narrower Ca:P) is recommended.…”
Section: Discussionmentioning
confidence: 88%
“…But, the efficacy of phytases can be limited by various factors including nutritional imbalances. One such limiting factor is dietary Ca ( Bedford and Rousseau, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a compromise in the quantity of Ca in over-processed MBM might have contributed to the higher litter score. Previous reports have suggested that feeding high Ca-diets increases the wetness of litter ( Bedford and Rousseau, 2017 ). Also, in the present study, the challenge increased DM of the litter while decreasing hock burns in the birds.…”
Section: Discussionmentioning
confidence: 99%